Beyond the Competence Agenda and the Cause for Relevance in Education - Mwinzi, Joseph Munyoki (Universitas PGRI Madiun, 2024)
In its inherent nature, education is envisaged to equip the learner with ideas to enhance creativity and upscale the skills to decipher and integrate fully to the intelligible and contingent world. The contemporary world has diverted attention towards aligning education to serve the competence agenda in form of economic commodity which can be bought or sold. Thus, the praxis of education is abstracted from the cause for relevance as defined by acquiring, inferring, and epitomizing in form of transfer to industry. It follows necessarily that education for its own sake is defied by commodification and commercialization. It is at this point that the concept of the cause for relevance in education is abrogated in education. This explains why this treatise draws attention to the question about how relevant is the cause of relevance in education against competence agenda? It is notable that competence agenda confuses education with training. Hence, the relevance cause in education can facilitate construal, customize, replicate or simulate education into precision, and attune the potentiality of the learner to new possibilities